Determinants of systolic blood pressure in Indonesian elderly men: In factor analysis perspective (A study in four Indonesian big cities) (Medical Journal of Indonesia, 2006)
The objective of this study was to assess the determinants of systolic blood pressure in elderly men. A cross sectional study was undertaken in 4 big cities in Indonesia using multistage random sampling. The respondents were 320 elderly men who were the sub-sample of 981 sample of a larger population study. Data were collected through anthropometric measurements, biochemical blood analysis, nutrient intake assessment, activity index and stress score. Two type of statistical analysis techniques were used to determine the determinants of systolic blood pressure in elderly men; multiple regression analysis and factor analysis. This study shows that determinants of systolic blood pressure, analyzed with these two types of analysis, multiple regression and factor analysis, resulting in no contradictory result. Direct multiple regression analysis to all independent variables showed that there was correlation between systolic blood pressure with fat mass, and LDL cholesterol. Multiple regression analysis to components resulting from factor analysis showed that there was positive correlation between systolic blood pressure with fat mass, body mass index (BMI), sum of skin-folds and waist circumference. (Med J Indones 2006; 15:115-20)